Prescribing pattern and prescription-writing quality of antineoplastic agents in the capital city of a middle-income developing country - Maryam Taghizadeh-Ghehi (Journal of Research in Pharmacy Practice, 2018)
Objective: Cancer is a global health concern with growing incidence worldwide. Chemotherapy is the main treatment modality in many malignancies. This study aimed at evaluation of antineoplastic prescribing pattern and prescription-writing quality in the capital city of Iran. Methods: All dispensed chemotherapy prescriptions by four main authorized pharmacies in Tehran during 1 month were targeted. Prescriptions with no antineoplastic medications or written by specialties other than oncology-related fields were excluded from the study. From the total 10,944 eligible prescriptions, 2736 (25%) prescriptions were selected randomly for data extraction. Findings: Total 5784 antineoplastic medications were written by 239 physicians; most of them were adult hematologist–oncologist (69.0%) and male (86.6%). Each prescription contained an average of 1.8 (±0.9) antineoplastic medications. The most widely prescribed antineoplastic agents were cyclophosphamide (16.2%), fluorouracil (15.2%), doxorubicin (12.8%), and oxaliplatin (11.0%). The quality of prescription writing was poor; diagnosis, drug dosing, treatment schedule, and instructions were mostly absent. Sixty percent of drugs were written in brand names. Conclusion: The prescribing writing quality was poor and patients were at great risk of medication errors. Prompt action including policies and educational strategies should be taken to assure effective and safe patient treatment with antineoplastic medications.